2017
DOI: 10.1007/s12325-017-0615-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation During Resuscitation: How Manual Chest Compressions Affect a Ventilator’s Function

Abstract: Parts of this study were supported by Weinmann Emergency Medical Technology GmbH + Co.KG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…While we found the turbine-driven ventilator to perform best, both pneumatic ventilators missed the preset tidal volume by almost a third. This compares to the results of a manikin study [ 16 ] and corresponds to the suspicion of hypoventilation in our previous clinical studies of blood gases in OHCA [ 26 , 27 ]. These found that contrary to the common perception of hyperventilation in CPR, hypocapnia leading to alkalosis was not observed at all.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…While we found the turbine-driven ventilator to perform best, both pneumatic ventilators missed the preset tidal volume by almost a third. This compares to the results of a manikin study [ 16 ] and corresponds to the suspicion of hypoventilation in our previous clinical studies of blood gases in OHCA [ 26 , 27 ]. These found that contrary to the common perception of hyperventilation in CPR, hypocapnia leading to alkalosis was not observed at all.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, chest compressions are a counteracting force to positive pressure ventilation and may limit inspiratory volumes [ 16 ]. The risk of hypoventilation in CPR has been recently illustrated by Duchatelet et al [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrated that CCSV significantly improved arterial oxygenation and better maintained arterial blood pressure during CPR when compared with the IPPV mode ( 8 ). Recently, Speer et al ( 21 ) demonstrated that CCSV delivered a significantly higher frequency of correct ventilation parameters without exceeding the upper pressure preset when compared with the IPPV mode during manual chest compression in a simulation model. In the present study, the same parameters of CCSV and IPPV were set based on the above-mentioned two studies, and the similar results were observed: CCSV significantly increased blood oxygenation, and partly improved blood circulation during CPR compared with the IPPV group.…”
Section: Discussionmentioning
confidence: 99%
“…The use of bi-level ventilation itself can be seen as controversial, since this is primarily described as a non-invasive ventilation mode, often used to support infants or patients suffering from respiratory failure (22) . Additionally, this mode has been shown to produce increased inspiratory pressures, when applied during CPR (23) . Although we could not observe these pressure peaks in our study and have no indication of resulting pulmonary damage, a specific pressure profile analysis might be warranted in future studies.…”
Section: Mmims-miget Measurements Showed Significantly Less Shunt Volmentioning
confidence: 99%